Particulate emissions from gasoline direct injection engines - Leach, FCP (2014)
Direct injection spark ignition (DISI) engines are the next generation of gasoline fuelled engines. Their greater fuel economy and reduced CO2 emissions compared with port fuel injection (PFI) engines has led to their popularity. However, DISI engines produce a greater number of particulate matter (PM) emissions than PFI engines. Concern over the health effects of PM emissions, and forthcoming European legislation to regulate them from gasoline powered vehicles has led to an increased interest in the study of PM formation, measurement, and characterisation. A model was developed by Aikawa et al, the PM index, correlating PM emissions with fuel composition. PM emissions are thought to be linked both to the vapour pressure (VP) and the double bond equivalent (DBE) of the components of the fuel. However, there was no independent control of these parameters and the study was undertaken on a PFI engine. In this thesis, experiments have been conducted to validate this model and extend it, as the PN index, to DISI engines. Fuels have been designed using Raoult’s law and UNIFAC (with careful consideration of octane number) such that the DBE and VP of the fuel mix could be varied independently. The design of the fuels was such that the component parts would co-evaporate upon injection into the cylinder, ensuring a homogeneous mixture of the components at the point of ignition. The PN index has been tested on a single cylinder engine, at a matrix of test points, using these model fuels, and their PM emissions have been analysed using a Cambustion DMS500. The results show that the PN index is followed closely using model fuels, provided that these model fuels contain a ‘light-end’ (in this case 5 % v/v n-pentane). Imaging of in-cylinder evaporation and in-cylinder measurement of hydrocarbons shows how the composition of model fuels affects their PM emissions. The PN index has also been tested using commercial fuels on a single cylinder engine and a Jaguar V8 engine; the results again show that the PN index is also an excellent predictor of PN emissions for market fuels from both of these engines. PN emissions have been evaluated from two fuels representing the EU5 reference fuel specification, developed using the PN index to give a difference in PM emissions. Testing these fuels on both a single cylinder engine and a Jaguar V8 engine has shown up to a factor of three variation in observed PN emissions. This has important implications for forthcoming European emissions legislation. The results of these tests were fed into the recommendations for the EU6 reference fuel specification. The PN index has also been investigated in a Jaguar V6 engine with five different fuels with a spread of calculated PN indices over a simulated NEDC. Here the PN emissions have been measured using two PN, and one PM instrument and the results compared. The results show that the trends of the PN index are followed, but not as closely as predicted. Detailed analysis shows that this discrepancy is due to other effects, for example cold start, dominating the PN emissions in certain phases. PN emissions have been measured from a highly boosted engine at a variety of operating points using 14 different fuels. It has been shown that for a large variety of engine operating parameters PN emissions from highly boosted engines behave as expected. When changing the fuels, the results show that a variation of over three orders of magnitude can be observed. The predictions of the PN index are inconclusive however, with further work suggested to fully evaluate the PN index on highly boosted engines.